2017
DOI: 10.1093/femsyr/fox030
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas system for yeast genome engineering: advances and applications

Abstract: The methods based on the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated (Cas) system have quickly gained popularity for genome editing and transcriptional regulation in many organisms, including yeast. This review aims to provide a comprehensive overview of CRISPR application for different yeast species: from basic principles and genetic design to applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
134
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(136 citation statements)
references
References 78 publications
2
134
0
Order By: Relevance
“…Of course one cannot also fail to mention the variants of CRISPR/Cas9 gene editing technology that allow almost unlimited tinkering (e.g. in yeast [309,310]). …”
Section: Control Factor Expression Engineeringmentioning
confidence: 99%
“…Of course one cannot also fail to mention the variants of CRISPR/Cas9 gene editing technology that allow almost unlimited tinkering (e.g. in yeast [309,310]). …”
Section: Control Factor Expression Engineeringmentioning
confidence: 99%
“…Another major limitation is the relatively low copy numbers of gRNA expressing plasmid in industrial yeast strains. So far, several strategies have been adopted for the expression of Cas9 and gRNA and most of the studies have found it necessary to express gRNA on a 2 μ based multicopy plasmid for efficient genome engineering in S. cerevisiae (DiCarlo et al, ; Stovicek et al, ; Stovicek, Holkenbrink, & Borodina, ). Interestingly, although the 2 μ‐based plasmids generally have relatively high copy numbers (20–30 copies/cell) with auxotrophic markers (i.e., HIS3 , TRP1 , LEU2 , and URA3 ), they can be as low as 3–5 copies/cell when antibiotic markers (i.e., KanMX and HygB ) are included (Karim, Curran, & Alper, ; Lian, Jin, & Zhao, ).…”
Section: Introductionmentioning
confidence: 99%
“…Another major limitation is the relatively low copy numbers of gRNA expressing plasmid in industrial yeast strains. So far, several strategies have been adopted for the expression of Cas9 and gRNA and most of the studies have found it necessary to express gRNA on a 2 μ based multicopy plasmid for efficient genome engineering in S. cerevisiae (DiCarlo et al, 2013;Stovicek et al, 2015;Stovicek, Holkenbrink, & Borodina, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Of particular relevance is the development of optimized CRISPR-Cas9 methods to engineer diploid and polyploid industrial yeast strains (Stovicek, Borja, Forster, & Borodina, 2015;Zhang et al, 2014). The history and various applications of genome editing have been discussed in-depth in the following reviews by Fraczek, Naseeb, and Delneri (2018) and Stovicek, Holkenbrink, and Borodina (2017).…”
Section: Crispr For Rapid Multiplex Engineering Of Cell Factoriesmentioning
confidence: 99%